The relevance of testing the efficacy of anti-angiogenesis treatments on cells derived from primary tumors: a new method for the personalized treatment of renal cell carcinoma. - Renaud Grépin (PLoS ONE, 2014)
Despite the numerous available drugs, the most appropriate treatments for patients affected by common or rare renal cell carcinomas (RCC), like those associated with the Xp11.2 translocation/transcription factor for immunoglobulin heavy-chain enhancer 3 (TFE3) gene fusion (TFE3 RCC), are not clearly defined. We aimed to make a parallel between the sensitivity to targeted therapies on living patients and on cells derived from the initial tumor. Three patients diagnosed with a metastatic RCC (one clear cell RCC [ccRCC], two TFE3 RCC) were treated with anti-angiogenesis drugs. The concentrations of the different drugs giving 50% inhibition of cell proliferation (IC50) were determined with the Thiazolyl Blue Tetrazolium Bromide (MTT) assay on cells from the primary tumors and a reference sensitive RCC cell line (786-O). We considered the cells to be sensitive if the IC50 was lower or equal to that in 786-O cells, and insensitive if the IC50 was higher to that in 786-O cells (IC 50 of 6 ± 1 µM for sunitinib, 10 ± 1 µM for everolimus and 6 ± 1 µM for sorafenib). Based on this standard, the response in patients and in cells was equivalent. The efficacy of anti-angiogenesis therapies was also tested in cells obtained from five patients with non-metastatic ccRCC, and untreated as recommended by clinical practice in order to determine the best treatment in case of progression toward a metastatic grade. In vitro experiments may represent a method for evaluating the best first-line treatment for personalized management of ccRCC during the period following surgery.